Penerapan Manajemen Mutu Dari Sumber Daya Manusia (People) Untuk Mengurangi Risiko Pekerjaan Ulang (Rework) - (Jurusan Teknik Sipil Politeknik Negeri Semarang), Suparno (Teknis, 2014)
Rework can not be separated from the world of construction. It is rare, if not impossible, to meet not rework the implementation of a construction project. Rework can have a negative impact on performance and productivity, both consultants and contractors. In addition, as described several sources, rework is one of the major contributors to cost overruns and project delays. The impact of the direct costs arising out significantly. In addition to direct costs, rework is also an indirect impact. Administrative costs (such as overhead and paperwork) and declining productivity, motivation and morale of workers and personnel are few examples of these indirect effects. In Indonesia alone, rework has been indicated as the second leading cause of loss of productivity, especially for workers, and is a frequent problem arising in the design and construction work and project delays. Taking into account that the adverse effects of a given large enough, then efforts to reduce rework in the construction phase is indispensable. However, achieving this goal will not work properly if the business is sporadic, without first studying its causes.Keywords : rework, document design, construction, quality management, human resources.